Natal homing in juvenile loggerhead turtles (Caretta caretta) - BOWEN, BRIAN W.; BASS, ANNA L.; CHOW, SHAIO-MEI; BOSTROM, MEREDITH; BJORNDAL, KAREN A.; BOLTEN, ALAN B.; OKUYAMA, TOSHINORI; BOLKER, BENJAMIN M.; EPPERLY, SHERYAN; LACASELLA, ERIN; SHAVER, DONNA; DODD, MARK; et al. (Molecular ecology, 2004)
Juvenile loggerhead turtles (Caretta caretta) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences (N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea (N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (ΦST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.